The Effect of Competency, Motivation and Work Discipline on Employee Performance (Study on Room Division V Hotel Bandung Employees) - Sumina, Mina; Komar Priatna, Deden; Fitri Anggraeni, Annisa (Dinasti Research & Yayasan Dharma Indonesia Tercinta (DINASTI), 2023)
The purpose of this study was to analyze the influence in competence, motivation, and work discipline on employee performance of Room Division V Hotel Bandung both simultaneously and partially. The research method used is descriptive and verification analysis using Likert scale with ordinal measurement.. Testing the validity and reliability used is the Product Moment correlation approach from Person, with saturated sample design of 35 respondents. Whereas the data analysis technique uses statistical data analysis with path analysis formula. The ordinal scale data are transformed into interval scale data through Successive Interval Method. Based on the results of hypothesis testing, it can be seen that competence, motivation, and work discipline simultaneously have a real and positive influence on employee performance at 59.5% while the remaining 40.5% are influenced by other variables. Partial testing revealed that competence not had a significant on employee performance work motivation had had a significant on employee performance with an effect of 25.5%, and work discipline had a significant and positive effect on employee performance with an effect of 51.5%.